Influência da umidade nas propriedades mecânicas dos compósitos poliméricos híbridos (sisal/ vidro) - Silva, Camila Cruz da (2012)
This study aims to evaluate the mechanical properties of polymer matrix composites reinforced with sisal fabric bidirectional tissue (Agave sisalana,) and E-glass fibers, containing the following configuration: a polymer matrix hybrid composite (Polyester Resin orthophalic) reinforced with three (3) layers of glass fibers and alternating-2 (two) layers of bidirectional sisal fabric, and finally a composite of polymer matrix reinforced with five (5) layers of glass fiber mat-type E. For this purpose as first step, the preparation of by sisal, since they are not on the market. The composites were made by manual lamination (Hand lay-up) and evaluated for tensile properties and three point bending both in the dry, and wet conditions aswele as immersed in oil. Macroscopic and microscopic characteristics of the materialsweve awalysed, after the completion of the mechanical tests. After the studies, it was proven that the sisal fiber decreases the tensile stiffness of the material above 50% for both situations studied the tensile strength of the material decreases by approximately 40% for the cases mentioned, and when compared to the specific strength stiffness values drop to 14.6% and 29.02% respectively for the dry state only. Constants for bending the values were are to approximately 50% to 25% for strength and stiffness of the material for the cases dry, wet and immersed in oil. Under the influence of tension fluids do not interfere in the stiffness of the material for the bending tests, the same does not occur with the resistance, and these values are modified only in the cases stiffness and flexural strength